ANALYSIS OF PSYCHOSOCIAL AND ECONOMIC CONSEQUENCES OF VESICO VAGINAL FISTULA AMONG WOMEN IN KEBBI STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Vesico Vaginal Fistula (VVF) is a devastating medical condition due to unrelieved obstructed labour and early marriage causing devastating social, economic and psychological effects on the health and wellbeing of women. This study seeks to analyse the psychosocial and economic consequences of VVF on women in Kebbi State. Using purposive sampling technique, a total of 50 questionnaire was administered to women aged 15 years and older. Data was analysed using descriptive and inferential statistics. Pearson correlation analysis was use to assess the degree of association or effects between the variables. The results shows that psychosocial consequences of VVF for r-calculated across all variables stigmatization .287* at 0.002 alpha level revealed strong effects across all variables on the demographic characteristics of respondents. While the economic consequences of VVF for r-calculated across all variables insolvency .200 at 0.002 alpha levels also revealed sturdy effects across all variables on demographic characteristics of the respondents. Furthermore, it has thus, been established that economic effects of VVF on the sufferers have more ravaging effects on the demographic characteristics of the respondents than the psychosocial effects. It is thus, recommended government, non-governmental agencies and the communities should embark on the provision of more support such as micro credit as well as social re-integration of VVF sufferers.
Keywords: Vesicovaginal fistula; VVF; Kebbi; Psychosocial; Economic consequences; Maternal health